Uranalysis as a means of diagnosis in veterinary diseases - Cheney, James Hamilton (My University, 1907)
Introduction: Since uranalysis has come to be a very important factor in the diagnosis of human diseases, it seems reasonable that it might be of some aid in veterinary practice. While it may not be practical for the veterinarian to be so precise or accurate in his calculations as is the human physician, it seems reasonable that he make some use of the subject. For example, it is a comparatively easy matter in the human practice to collect all the urine excreted in twenty-four hours, while in veterinary practice this would be attended with more difficulty. This difficulty:, however, may be remedied somewhat by taking the sample the first thing in the morning. If the composition of the urine is an index of what is going on in the tissues it remains only for us to be able to recognize healthy and diseased conditions and to be able to make the tests fairly accurately. If one becomes familiar with uranalysis and its significance it can be made as valuable a means of diagnosing many diseases as any of the other methods at our disposal.
Citation: Cheney, James Hamilton. Uranalysis as a means of diagnosis in veterinary diseases. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Uranalysis; Disease Diagnosis; Veterinary Practice; Theses